Pengelolaan Pariwisata Alam Berbasis Ajaran Palemahan Pada Penyedia Jasa Open Trip Pendakian Gunung Lawu - Rudiyanto; Sujaelanto; Resmitra Wisnu Wardhana (Samsara Institute Publisher, 2026)
The increasing number of climbers on Mount Lawu, particularly through open trip service providers, has led to environmental problems such as waste accumulation, water source pollution, and ecosystem damage. This study aims to describe the management and educational strategies implemented by open trip providers, identify supporting factors for the application of Palemahan teachings, and analyze the forms of collaboration between service providers and related institutions. A qualitative descriptive narrative approach was employed, involving five open trip providers operating on the Candi Cetho route: Oaoe Adventure, Tiga Dewa Adventure, Tebet Adventure, Green Lawu, and CFD Traveller. Data collection techniques included direct observation, in-depth interviews with owners, crew, guides, porters, participants, and informants from PUD (Regional Public Company) Aneka Usaha and Perhutani, as well as documentation studies. Data analysis used reduction, presentation, and conclusion drawing with source and technique triangulation. The study applies Cooper's 4A Tourism Destination Management Theory, Robert L. Kahn's Role Theory, and Emile Durkheim's Social Solidarity Theory. The findings indicate that management includes planning, implementation, evaluation, and supervision. Environmental education strategies are carried out through pre-climb briefings, role modeling, direct supervision, and the pack in pack out system with personal trash bags. Supporting factors include natural attractions, accessibility, facilities, environmental awareness, involvement of local porters, and social solidarity. The implementation of Palemahan values is realized through land protection, water conservation, fire control, waste management, and flora and fauna preservation. Collaboration with PUD (Perusahaan Umum Daerah) Aneka Usaha, Perhutani, village government, volunteers, and local communities plays a crucial role in waste management, conservation, supervision, and law enforcement.